Retention of international nurses in receiving country: Voices of Indonesian nurses in Japanese healthcare facilities - Ferry Efendi; Eka Mishbahatul Mar’ah Has; Rifky Octavia Pradipta; Grace Solely Houghty; Hisaya Oda; Yuko Tsujita (International Journal of Nursing Sciences)
Objectives: This study aimed to explore the voices of Indonesian migrant nurses on their retention in Japanese healthcare facilities. Methods: A descriptive qualitative study was conducted between June and September 2023. The snowball sampling method was utilized to recruit 22 Indonesian nurses working in healthcare facilities in seven prefectures of Japan. Semi-structured interviews were conducted based on their shared experiences. All interview data were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Six prominent themes and 15 subthemes emerged: 1) organizational factors (caring leader, involvement in decision making, career development, and participation in training); 2) social support systems (group support, colleagues support and friend support); 3) individual drive (lifelong learning and persistent); 4) national policies (government support in public service and flexibility in finding a comfortable placement); 5) family factors (positive support of child education and development and maintaining relationship with spouse); and 6) economic factors (staying due to high salary and increasing income streams). Conclusions: Retention of Indonesian migrant nurses in Japan is a multifaceted challenge that hinges on various interconnected factors. This study has gone some way toward enhancing our understanding of international nurse retention in the receiving countries. Corresponding supports at the individual, family, organizational, economic, social, and national policy levels should be considered to keep them in their destination countries.